2007
DOI: 10.1161/strokeaha.106.471805
|View full text |Cite
|
Sign up to set email alerts
|

Depressive Disorders After 20 Months in Elderly Stroke Patients

Abstract: Background and Purpose-Depression is common after stroke. Reported frequencies vary widely between studies because of differences in patient selection, time from stroke to assessment, evaluation methods and diagnostic criteria. Poststroke depression is related to increased mortality and poorer rehabilitation outcome. Few studies have been done in the elderly, and there is a lack of studies with population-based controls. We aimed to examine the risk of depression in elderly patients one and a half years after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
76
0
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 107 publications
(81 citation statements)
references
References 32 publications
2
76
0
3
Order By: Relevance
“…Written informed consent was obtained from all participants (or their guardians) prior to their involvement in the study. Study procedures have been reported M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 6 previously [21,22]. Patients were contacted by letter one year after the stroke.…”
Section: Methodsmentioning
confidence: 99%
“…Written informed consent was obtained from all participants (or their guardians) prior to their involvement in the study. Study procedures have been reported M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 6 previously [21,22]. Patients were contacted by letter one year after the stroke.…”
Section: Methodsmentioning
confidence: 99%
“…In clinical practice, only a minority of depressed patients are diagnosed and even fewer are treated [551]. Depression has been reported in up to 33% of stroke survivors, compared with 13% of age- and sex-matched controls [552], but reliable estimates of the incidence and prevalence of depression in a stroke cohort are limited [550]. Predictors of post-stroke depression in the rehabilitation setting include increasing physical disability, cognitive impairment and stroke severity [550].…”
Section: Rehabilitationmentioning
confidence: 99%
“…168 Depression is common after stroke. [169][170][171][172][173] A systematic review 169,170 found a pooled estimate of 33% for depression after stroke. In the study by Linden et al, 173 stroke was related to an odds ratio for depression of 3.2 in women and 4.0 in men 1.5 years after the index stroke.…”
Section: Cerebrovascular Diseasementioning
confidence: 99%